Brechas de la educación y su pertinencia en el tiempo - Iñiguez, Juan Fernando (2018)
This article analyzes the relevance of the education system, starting with conceptualizing and understanding it as an indispensable requirement for quality education, necessary to rethink education. The article explores education and its evolution over time, its interaction with the society of the time and its impact, social intentions concerning education, who the background and role that juice, its birth and its characteristics. From the university and school of the Middle Ages through the great educational heyday of the modern school, through an analysis of the de-centralization and projection of today's education and its needs.It is necessary to examine the time to transform today's education, to project an education ofthe future with new perspectives that fulfills the much-desired relevance to society, industry, politics and culture, integrating problems to be source of solutions, an education with greater presence and influence that from the university generates new forms of learning and knowledge for basic education systems and is projected universal, intercultural and inclusive